2010
DOI: 10.1088/0004-637x/709/2/975
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Density Distribution in the Molecular Gas Toward Westerlund 2: Further Evidence for Physical Association

Abstract: Furukawa et al. (2009) reported the existence of a large mass of molecular gas associated with the super star cluster Westerlund 2 and the surrounding HII region RCW49, based on a strong morphological correspondence between NAN-TEN2 12 CO(J=2-1) emission and Spitzer IRAC images of the HII region. We here present temperature and density distributions in the associated molecular gas at ∼3.5 pc resolution, as derived from an LVG analysis of the 12 CO(J=2-1), 12 CO(J=1-0) and 13 CO(J=2-1) transitions. The kinetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
121
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 29 publications
10
121
0
Order By: Relevance
“…Dame (2007) observed Westerlund 2 with the CfA 1.2 m telescope using 12 CO(J = 1-0) survey data and found a possible association with a giant molecular cloud (GMC) on the far side of the Carina spiral arm, at a distance of 5.0 kpc. Observations at a higher resolution (90 ) on the J = 2-1 transition of 12 CO performed by the Nanten 2 4-m sub-millimeter telescope Ohama et al 2010) confirm the Dame (2007) results but also suggest another possible association. A significant clump of molecular gas, consisting of a foreground component at 0 km s −1 is found, with a mass of (9.1 ± 4.1) × 10 4 M , and a background component at 16 km s −1 , with a mass of (8.1 ± 3.7) × 10 4 M , both of which are claimed to be connected with RCW 49, at a distance of 5.4 +1.1 −1.4 kpc.…”
Section: Introductionmentioning
confidence: 56%
“…Dame (2007) observed Westerlund 2 with the CfA 1.2 m telescope using 12 CO(J = 1-0) survey data and found a possible association with a giant molecular cloud (GMC) on the far side of the Carina spiral arm, at a distance of 5.0 kpc. Observations at a higher resolution (90 ) on the J = 2-1 transition of 12 CO performed by the Nanten 2 4-m sub-millimeter telescope Ohama et al 2010) confirm the Dame (2007) results but also suggest another possible association. A significant clump of molecular gas, consisting of a foreground component at 0 km s −1 is found, with a mass of (9.1 ± 4.1) × 10 4 M , and a background component at 16 km s −1 , with a mass of (8.1 ± 3.7) × 10 4 M , both of which are claimed to be connected with RCW 49, at a distance of 5.4 +1.1 −1.4 kpc.…”
Section: Introductionmentioning
confidence: 56%
“…Due to the size difference between the two clouds, the shock front becomes oblique as the clouds merge, pressing down on the shocked disk to form a crescent structure that is commonly observed in observations of suspected cloud-cloud collision events (Ohama et al 2010;Furukawa et al 2009). …”
Section: Discussionmentioning
confidence: 96%
“…Their formation has historically perplexed researchers due to the problem of creating such a high-mass cluster if the star formation efficiency inside the GMC is low. The first cluster to be identified as a possible collision object was Westerland 2, which was observed by Furukawa et al (2009) and Ohama et al (2010) and found to have two associated clouds with relative velocity of 20 km s −1 . The authors propose that the resulting shock between the clouds compressed the gas to produce the massive star cluster.…”
Section: Observational Evidence For Cloud-cloud Collisionsmentioning
confidence: 99%
“…The studies of the molecular hydrogen by Dame (2007), Furukawa et al (2009) and Ohama et al (2010) show a complex environment around Westerlund 2. Two molecular clouds in the velocity ranges of [-11 : 9] km/s and [11: 21] km/s physically coincide with Westerlund 2 and and the large H ii region RCW 49.…”
Section: Gas Around Westerlundmentioning
confidence: 99%